Scientist, artist and collector: Semblanza on the life and work of Dr. Yoav Bashan - Espinosa Victoria, David (REVISTA TERRA LATINOAMERICANA, 2019)
This semblance is a post mortem tribute that the Mexican Society of Soil Science A. C. (SMCS), concedes to Dr. Yoav Bashan, one of the most prominent researches of soil microorganisms. Dr. Bashan was born on October 12, 1951 in Haifa, Israel and died on September 19, 2018 in Auburn, Alabama, U.S.A. He was an active researcher of the interaction among plant growth promoting bacteria, plants of anthropogenic importance and the environment. Due to his hard work, in 2013, he was awarded by the SMCS, A.C. with the “Award for Merit in Soil Biology Dr. Jesús Caballero Mellado”. Two little-known facets of Dr. Bashan were his passion for painting and the hobby for collecting handicrafts. His scientific legacy is recorded in the annals of the Terra Latinoamericana journal, the official magazine of scientific outreach of the SMCS, A. C., as well as many journals around the world (Figure 1).